Unkeito promotes follicle development by restoring reduced follicle-stimulating hormone responsiveness in rats with polycystic ovary syndrome - Yoshita, Sayako; Osuka, Satoko; Shimizu, Tomofumi; Fujitsuka, Naoki; Matsumoto, Chinami; Bayasula,; Miyake, Natsuki; Muraoka, Ayako; Nakanishi, Natsuki; Nakamura, Tomoko; Goto, Maki; Kajiyama, Hiroaki (Frontiers in Endocrinology, 2023)
Background Polycystic ovary syndrome (PCOS) is a common disorder resulting in irregular menstruation and infertility due to improper follicular development and ovulation. PCOS pathogenesis is mediated by downregulated follicle-stimulating hormone receptor (FSHR) expression in granulosa cells (GCs); however, the underlying mechanism remains elusive. Unkeito (UKT) is a traditional Japanese medicine used to treat irregular menstruation in patients with PCOS. In this study, we aimed to confirm the effectiveness of UKT in PCOS by focusing on follicle-stimulating hormone (FSH) responsiveness. Methods A rat model of PCOS was generated by prenatal treatment with 5α-dihydrotestosterone. Female offspring (3-week-old) rats were fed a UKT mixed diet or a normal diet daily. To compare the PCOS phenotype in rats, the estrous cycle, hormone profiles, and ovarian morphology were evaluated. To further examine the role of FSH, molecular, genetic, and immunohistological analyses were performed using ovarian tissues and primary cultured GCs from normal and PCOS model rats. Results UKT increased the number of antral and preovulatory follicles and restored the irregular estrous cycle in PCOS rats. The gene expression levels of FSHR and bone morphogenetic protein (BMP)-2 and BMP-6 were significantly decreased in the ovarian GCs of PCOS rats compared to those in normal rats. UKT treatment increased FSHR staining in the small antral follicles and upregulated Fshr and Bmps expression in the ovary and GCs of PCOS rats. There was no change in serum gonadotropin levels. In primary cultured GCs stimulated by FSH, UKT enhanced estradiol production, accompanied by increased intracellular cyclic adenosine monophosphate levels, and upregulated the expression of genes encoding the enzymes involved in local estradiol synthesis, namely Cyp19a1 and Hsd17b. Furthermore, UKT elevated the expression of Star and Cyp11a1, involved in progesterone production in cultured GCs in the presence of FSH. Conclusions UKT stimulates ovarian follicle development by potentiating FSH responsiveness by upregulating BMP-2 and BMP-6 expression, resulting in the recovery of estrous cycle abnormalities in PCOS rats. Restoring the FSHR dysfunction in the small antral follicles may alleviate the PCOS phenotype.